Talbot images and Talbot spectra of a 2D orthogonal periodicity structure. (24th March 2016) - Han, Pin; Weng, Junhong
Abstract: The conditions for Talbot images and Talbot spectra associated with a 2D orthogonal periodicity structure are obtained with the transfer function method. It is found that the longitudinal distances to find the whole 2D Talbot images are the least common multiple of each of the individual 1D Talbot periodicities. Also, the transversal locations to find the Talbot spectra are given, where the detected spectra are identical to the incident one without the effect of diffraction. The spectral switches involved are also presented.